Paradoxical leadership, team adaptation and team performance: The mediating role of inclusive climate - Meng, Weixuan; Xu, Zhihao; Abuliezi, Zulayati; Lyu, Yaohui; Zhang, Qi (Frontiers in Psychology, 2023)
In an increasingly complex and changing competitive environment, organizations inevitably face various conflicting demands, such as the contradiction between the psychological needs of employees and the organization's performance requirements. Paradoxical leadership could focus on these competing needs of the organization and employees in multiple ways simultaneously. According to the trickle-down effect of Social Learning Theory, we investigated whether and how paradoxical leadership may increase team adaptation and team performance. The study had a time-lagged survey design and included 254 team members and 60 leaders in 60 work teams in mainland China. The results of the structural equation modeling analysis indicated that paradoxical leadership is an essential predictor of team adaptation and performance, and that inclusive climate is mediating in this relationship. Our findings reveal a mechanism underlying the benefits of paradoxical leadership on team adaptation and team performance from a team-level perspective.